Model kitchen and its departments - Swingle, Cora Edith (My University, 1900)
Introduction: The hope of our nation lies in the homes of its people to just the extent that these homes are what they should be. The question was once asked, “Does what people eat affect their moral natures”? The answer came “Most assuredly! After eating one of many of the dinners prepared at the present day, it would be impossible to live the Christian graces for the next twelve hours”. We may wonder why such a state of affairs continues, and we find that it is chiefly because it has always been so. The kitchen is the laboratory of the house, and in it are performed some of the most important duties. The object should be to supply the family with good, wholesome, palatable, digestible food that will build up and strengthen both body and mind. It is just as easy to have well prepared and thoroughly cooked food as a poorly prepared article, if one will but take pains to learn how; and it is often much easier to prepare wholesome digestible food than much of the heavy pastry that we find on our American tables. In many of the kitchens we find a lack of system, not only in the arrangement and adjustment of furniture and utensils, but also in the articles themselves. We find in many articles that a trained housekeeper would have no use for, and at the same time a great lack of useful and even necessary articles—necessary at least from her point of view. It is with this need in view that this thesis is written.
Citation: Swingle, Cora Edith. Model kitchen and its departments. Senior thesis, Kansas State Agricultural College, 1900.
Morse Department of Special Collections
Keywords: Home Economics; Kitchen; Kitchen Utensils; Kitchen Appliances; Kitchen Floor Plan; Theses